The influence of in vitro gastrointestinal digestion and fecal fermentation on the flowers of Juglans regia: Changes in the active compounds and bioactivities - Jin, Ximeng; Ru, Yuerong; Zhang, Xuechun; Kan, Huan; Xiang, Ping; He, Xuemei; Sun, Jian; He, Xiahong; Wang, Zhengxing (Frontiers in Nutrition, 2022)
The objective of the research was to investigate the digestion and fecal fermentation characteristics of the flowers of Juglans regia (FJR), by using in vitro simulated digestion model (oral, gastric, and intestine) as well as colonic fermentation. As a result, the contents of most active substances and functional activities of FJR were decreased as the digestion proceeded, and showed a trend of first increasing and then decreasing in the fecal fermentation phase. In the oral digestion phase, the total phenolic and total flavonoid contents were released most with the values of 11.43 μg/mg and 9.41 μg/mg, respectively. While in the gastric digestion phase, the antioxidant abilities, α-glucosidase and α-amylase inhibitory abilities were the weakest. By using high-performance liquid chromatography, 13 phenolic acids and 3 flavonoids were detected. Of these, the highest number of identified compounds were found in the undigested and the oral digestion stages, which were mainly salicylic acid, epicatechin, 3,5-dihydroxybenoic acid, vanillic acid, and protocatechuic acid. However, great losses were observed during the gastric and intestinal digestion stages, only protocatechuic acid, epicatechin, and salicylic acid were found. Surprisingly, fecal fermentation released more abundant phenolic substances compared to gastric and intestinal digestion. Additionally, FJR reduced the pH values in the colonic fermentation system, significantly promoted the production of short-chain fatty acids (SCFAs), such as acetic acid, and regulated the microbe community structure during fecal fermentation stage through improving community richness of beneficial microbiota. Further Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that FJR could suppress the metabolic pathways related to diseases, such as infectious diseases, metabolic diseases and neurodegenerative diseases. In conclusion, although the bioactivities of FJR decreased significantly after in vitro gastrointestinal digestion and fecal fermentation, it still maintained certain antioxidant and hypoglycemic activity in vitro. This study described the detailed changes in the active compounds and bioactivities of FJR during in vitro gastrointestinal digestion and fecal fermentation, and its effects on microbiota composition and SCFAs levels in feces. Our results revealed the potential health benefits of FJR, and could provide a reference for its further research and development.